2009
DOI: 10.1590/s1516-05722009000200013
|View full text |Cite
|
Sign up to set email alerts
|

Produção de mudas de Etlingera elatior (Jack) R.M. Sm. através da cultura de tecidos vegetais in vitro

Abstract: O uso de produtos naturais para o tratamento de doenças é algo que o ser humano já está habituado a realizar desde o início dos tempos. A utilização de Etlingera elatior (Bastão do Imperador), uma herbácea muito comum nos jardins e em áreas de banhado, para o tratamento de dores musculares e reumatismo é citada pela cultura popular, o que incentivou a indústria farmacêutica a começar a investir nos estudos sobre sua atividade. Porém, a produção de biomassa através de plantas sadias e de alta qualidade ainda é … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…When analyzing the behavior of this variable for light qualities, the white LED (4.57) was significantly higher when compared to fluorescent (3.30), stimulating the performance of this variable (Figure 1D). Plant characteristics, such as growth rate, development of vegetative and reproductive organs, total biomass and distribution of photoassimilates are affected by the quality of light (Posada et al, 2011), due to the specific wavelengths contribute to the increase of the amount of chlorophylls and carotenoids in the plants (Rocha et al, 2013).…”
Section: Resultsmentioning
confidence: 99%
“…When analyzing the behavior of this variable for light qualities, the white LED (4.57) was significantly higher when compared to fluorescent (3.30), stimulating the performance of this variable (Figure 1D). Plant characteristics, such as growth rate, development of vegetative and reproductive organs, total biomass and distribution of photoassimilates are affected by the quality of light (Posada et al, 2011), due to the specific wavelengths contribute to the increase of the amount of chlorophylls and carotenoids in the plants (Rocha et al, 2013).…”
Section: Resultsmentioning
confidence: 99%
“…Working with different concentrations of 6-BA for the in vitro propagation of Etlingera elatior, Rescarolli and Zaffari (2009) observed that their application did not induce the development of lateral buds, which can be justified by the plantlets high apical dominance and/or inefficiency of the of the cytokinin levels present in culture medium in altering the auxins/cytokinin relation in the tissues.…”
Section: Resultsmentioning
confidence: 99%